Spruce girdling decreases abundance of fungivorous soil nematodes in a boreal forest. (April 2021) - Kudrin, Alexey A.; Zuev, Andrey G.; Taskaeva, Anastasia A.; Konakova, Tatiana N.; Kolesnikova, Alla A.; Gruzdev, Ivan V.; Gabov, Dmitriy N.; Yakovleva, Evgenia V.; Tiunov, Alexei V.
Abstract: The relative importance of belowground and aboveground energy inputs for the decomposer communities in soil remains largely unknown. In particular, no research has been done on the significance of root-derived resources for nematode communities in boreal forests. In two spruce stands in the taiga zone, we set up a field experiment in which girdling of spruce trees and clipping of dwarf shrubs was performed. Root-derived resources were hypothesized to be highly important; accordingly, we expected to observe a suppression of the nematode community after experimental manipulations. To obtain information on the nature of changes in the soil food web, nematode community structure indices were applied. In partial confirmation of our hypothesis, spruce girdling decreased mycorrhizal hyphae biomass as assessed via in-growth mesh bags, as well as the abundance of fungivorous nematodes, mostly of the Aphelenchoides and Filenchus genera . The enrichment index (EI) value decreased, indicating reduction of organic matter inputs into the soil food web, whereas nematode channel ratio (NCR) index value increased, indicating a shift towards domination of the bacterial energy channel. Total nematode abundance, genera richness, and abundance of herbivores, omnivores, and predators did not change in response to spruce girdling. Clipping of dwarf shrubs decreased fungal and bacterial PLFA biomarkers, but did not affect nematode communities. Thus, the resources channeled in soil by the roots of canopy trees are of different relative importance for nematodes having different trophic habits. Fungivorous nematodes are at least partly dependent on root-derived resources, suggesting feeding on ectomycorrhizal mycelium. Rhizodeposits of understory vegetation are likely of low importance for nematodes. Highlights: We set up experiment in which spruce girdling and clipping of shrubs was performed. Spruce girdling decreased the abundance of fungivorous nematodes. Clipping of dwarf shrubs did not affect nematode communities.